Pengaruh Leverage, Profitabilitas, Dan Kepemilikan Institusional Terhadap Tax Avoidance - Noer Rahmi; Garin Pratiwi Solihati (STIE AUB Surakarta, 2025)
In Indonesia, tax revenues constitute roughly 80% of the country's overall governmental income. Authorities continuously strive to guarantee that tax collection achieves predetermined objectives. However, obstacles persist in optimizing tax effectiveness, potentially motivating taxpayers to adopt tax minimization practices. Tax minimization may be characterized as a method for diminishing fiscal responsibilities by taxpayers through reducing their tax burden while remaining within legal boundaries, or it may be described as taking advantage of gaps in current legislation. This study aims to investigate the effects of leverage, profitability, and institutional ownership on tax minimization practices within Consumer Non-Cyclical Sector companies listed on the Indonesia Stock Exchange between 2020-2023. This research adopts a quantitative approach. The research population encompasses non-cyclical consumer sector firms listed on the Indonesia Stock Exchange (IDX) from 2020-2023. The study employs purposive sampling methods, resulting in 164 data observations for examination. The analytical method utilized is multiple linear regression through IBM SPSS 25 software. Results indicate that leverage exhibits a significant positive effect on tax minimization, while profitability displays a significant negative effect on tax minimization, and institutional ownership fails to show a significant effect on tax minimization.